Women Face to Fear and Safety Devices During the COVID-19 Pandemic in Italy: Impact of Physical Distancing on Individual Responsibility, Intimate, and Social Relationship - Parisi, Rosa; Lagomarsino, Francesca; Rania, Nadia; Coppola, Ilaria (Frontiers in Public Health, 2021)
The COVID-19 pandemic of 2020 in Italy had its first epidemic manifestations on January 31, 2020. The socio-sanitary rules imposed by the government concerned the social distance and management of intimate relationships, the sense of individual responsibility towards public health. Physical distancing and housing isolation have produced new representations of intrafamily, generational, neighborhood, community responsibility, bringing out a new “medicalized dimension” of society. In light of this contextual framework, the research aims are: to analyze how: the perception of individual responsibility for public and familial health and physical distancing redraws the relation between subjects-family-community; the State's technical-health intervention reformulated the idea of social closeness, but also how the pandemic fear and social confinement has re-evaluated a desire for community, neighborhood, proximity; during the lockdown families, friends, neighbors have reconstructed feelings of closeness and forms of belonging. The methodology used is quanti-qualitative and involved 300 women through an online questionnaire. The data collected highlight how the house during the lockdown is perceived as a safe place and how women implement both the recommendations and the behaviors aimed at preventing contagion, but also ways that allow coping with the situation from a perspective of well-being. Furthermore, the data show how the dimension of distancing has loosened the relational dimension outside the family unit, with a greater distancing compared to pre-pandemic data. However, the majority of women report that they have joined solidarity initiatives, demonstrating that they want to maintain ties and participate actively in community life.